The biological function of m6A methyltransferase KIAA1429 and its role in human disease - Xiaoyu Zhang; Meng jiao Li; Lei Xia; Hairong Zhang (PeerJ, 2022)
KIAA1429 is a major m6A methyltransferase, which plays important biological and pharmacological roles in both human cancer or non-cancer diseases. KIAA1429 produce a tumorigenic role in various cancers through regulating DAPK3, ID2, GATA3, SMC1A, CDK1, SIRT1 and other targets, promoting cell proliferation, migration, invasion, metastasis and tumor growth . At the same time, KIAA1429 is also effective in non-tumor diseases, such as reproductive system and cardiovascular system diseases. The potential regulatory mechanism of KIAA1429 dependent on m6A modification is related to mRNA, lncRNA, circRNA and miRNAs. In this review, we summarized the current evidence on KIAA1429 in various human cancers or non-cancer diseases and its potential as a prognostic target.